Multi-robot cooperation for lunar In-Situ resource utilization - Martinez Rocamora, Bernardo; Kilic, Cagri; Tatsch, Christopher; Pereira, Guilherme A. S.; Gross, Jason N. (Frontiers in Robotics and AI, 2023)
This paper presents a cooperative, multi-robot solution for searching, excavating, and transporting mineral resources on the Moon. Our work was developed in the context of the Space Robotics Challenge Phase 2 (SRCP2), which was part of the NASA Centennial Challenges and was motivated by the current NASA Artemis program, a flagship initiative that intends to establish a long-term human presence on the Moon. In the SRCP2 a group of simulated mobile robots was tasked with reporting volatile locations within a realistic lunar simulation environment, and excavating and transporting these resources to target locations in such an environment. In this paper, we describe our solution to the SRCP2 competition that includes our strategies for rover mobility hazard estimation (e.g. slippage level, stuck status), immobility recovery, rover-to-rover, and rover-to-infrastructure docking, rover coordination and cooperation, and cooperative task planning and autonomy. Our solution was able to successfully complete all tasks required by the challenge, granting our team 6th place among all participants of the challenge. Our results demonstrate the potential of using autonomous robots for autonomous in situ resource utilization (ISRU) on the Moon and the effectiveness of realistic simulation environments for testing and validating robot autonomy and coordination algorithms.